Identifying DOC gains and losses during a 20-year record in the Trout Beck catchment, Moor House, UK. (September 2016) - Moody, C.S.; Worrall, F.; Burt, T.P.
Highlights: Two models of DOC concentrations within an ECN catchment at Moor House NNR. Single tracer regression model showed DOC loss between source and catchment outlet. Longer in-stream residence time, warm soil and summer months had larger DOC losses. PCA model showed DOC gain, attributed to an unmeasured groundwater contribution. Abstract: The turnover of organic carbon in rivers could represent a large source of greenhouse gases to the atmosphere and studies have suggested that of the order of 70% of the dissolved organic carbon exported from soils could be lost in rivers before it flows to continental seas. The Environmental Change Network (ECN) monitoring of the dominantly peat-covered Trout Beck catchment within the Moor House site enabled the amount of dissolved organic carbon (DOC) lost within a stream over a 20-year period to be estimated. The study compared DOC concentrations of precipitation, shallow and deep soil waters with those at the catchment outlet. The mass balance between source and outlet was reconstructed by two methods: a single conservative tracer; and based upon a principal component analysis (PCA) using multiple tracers. The study showed the two methods had different outcomes, with the PCA showing a DOC gain and the single tracer showing a DOC loss. The DOC gain was attributed to an unmeasured groundwater contribution that dominates when the river discharge is lower. The DOC loss was related to the in-stream residence time, the soil temperature and month of the year, with longer in-stream residence times, warmer soils and summer months having larger DOC losses. The single tracer study suggested a 10 year average loss of 8.77 g C m −2  year −1, which is 33.1 g CO2eq m −2  year −1, or 29% of the DOC flux from the source over a mean in-stream residence time of 4.33 h.